Situating H.D. Thoreau's _Walden_ within Post-Exceptionalist American Studies. Exceptionalism Reconsidered - Šesnić, Jelena (2013)
As a reaction to the latest revisionary trend within American studies challenging the notion of US exceptionalism, the article looks at ways of reading "hypercanonized" US texts, such as H.D. Thoreau's _Walden_, from the vantage point of world-systems theory and comparative literature methodology. It is argued that new methodologies complicate readings of classic US texts and align them with other "planetary" or global literary phenomena.
Projekt MZOS
ENG